The methods to intensify waste decomposition = Metody intensyfikacji degradacji odpadów - Suchowska-Kisielewicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Landfilling is still a popular waste disposal method. However, currently it is insufficient practice for effective waste management. Conventional waste disposal leads to pollutant emissions by a long periods of time and requires applying specific emission control and treatment method. Old landfill might require aftercare for decades or centuries.
Keywords: zagospodarowanie odpadów; składowiska; emisja zanieczyszczeń; recylkulacja odcieków; degradacja odpadów; landfills; leachate; municipal solid waste; mechanical biological treatment wastes; recirculation; aerobic degradation